1997
DOI: 10.1002/masy.19971150108
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of stabilizers during oxidation processes

Abstract: The antioxidative action of mixtures of phenols, phosphites, HALS, and some of their transformation products in various compositions has been studied in the thermo-and photooxidation of hydrocarbons and polypropylene under different conditions. In the AIBN-initiated oxidation of hydrocarbons at low temperatures (< 8OoC), hindered phenols, hindered aryl phosphites and the nitroxyl derivatives of HALS act antioxidatively when used individually in appropriate concentrations. Secondary HALS do not show any inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Ohkatsu et al have proposed a synergistic action mechanism of these additives for preventing the photo‐degradation process of plastics, which including regeneration of phenols from quinones under UV irradiation in the presence of HALS, which is promoted by UV light. It was also suggested that the mechanism for synergism between hindered phenol and HALS in bifunctional stabilizer AG‐HDM differed from that in a mixture of hindered phenol and HALS . In this article, one of advantages of AG‐HDM in SPA6‐2 over the combination of AG and HDM in SPA6‐1 is that less condensation water is formed during processing and thermal‐oxidative degradation.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Ohkatsu et al have proposed a synergistic action mechanism of these additives for preventing the photo‐degradation process of plastics, which including regeneration of phenols from quinones under UV irradiation in the presence of HALS, which is promoted by UV light. It was also suggested that the mechanism for synergism between hindered phenol and HALS in bifunctional stabilizer AG‐HDM differed from that in a mixture of hindered phenol and HALS . In this article, one of advantages of AG‐HDM in SPA6‐2 over the combination of AG and HDM in SPA6‐1 is that less condensation water is formed during processing and thermal‐oxidative degradation.…”
Section: Resultsmentioning
confidence: 93%
“…Hindered phenol is an important class of primary antioxidants for PA6, although the efficiency of which is not as good as that in polyolefins . Binary systems composed of a hindered phenol as the primary AO and a phosphite‐based compound as the secondary AO, which have significant synergistic effect, are often used as traditional thermal‐oxidative stabilizing systems for PA6 . Hindered amine light stabilizers (HALS) have been used widely as antioxidants .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in the case of the sterically hindered phenols and amines) and their inhibiting action in the hypoxic polymer environment are undoubtedly more pronounced than that in the liquid phase. But on the other hand they cause discoloration of the polymer during processing [17,18].…”
Section: Introductionmentioning
confidence: 99%